Oral microbial biofilm models and their application to the testing of anticariogenic agents. (July 2016) - Sim, Christina P.C.; Dashper, Stuart G.; Reynolds, Eric C.
Abstract: Objectives: This review paper evaluates the use of in vitro biofilm models for the testing of anticariogenic agents . Data: Caries is a biofilm-mediated oral disease and in vitro biofilm models have been widely utilised to assess how anticariogenic or antimicrobial agents affect the de/remineralisation process of caries. The use of enamel or dentine substrata has enabled the assessment of the relationship between bacterial activity and caries lesion initiation and progression and how this relationship could be affected by the agent under study. Sources: Only papers published in the English literature were reviewed. Study selection: Both 'open' and 'closed' biofilm systems utilising either single or multiple-species as defined or undefined inocula are analysed. Conclusions: There is a wide variety of in vitro biofilm models used in the assessment of anticariogenic agents. A reproducible model that mimics the shear forces present in the oral environment, and uses a defined multiple-species inocula on tooth substrates can provide valuable insight into the effectiveness of these agents. Clinical relevance: Biofilm models are important tools for the testing of the mechanism of action and efficacy of novel anticariogenic agents. Results from these experiments help facilitate the design of randomised, controlled clinical trials for testing of efficacy of the agents to provide essential scientific evidence for their clinical use.